Морфогенез кісток скелету щурів на тлі тривалого вживання тартразину та можливості його корекції = Morphogenesis bones rats against long tartrazine use and possibilities of its correction = Морфогенез костей скелета крыс на фоне длительного употребления тартразина и возможность его коррекции - Lukjantseva, Galina (Journal of Education, Health and Sport, 2016)
Lukjantseva Galina Морфогенез кісток скелету щурів на тлі тривалого вживання тартразину та можливості його корекції = Morphogenesis bones rats against long tartrazine use and possibilities of its correction = Морфогенез костей скелета крыс на фоне длительного употребления тартразина и возможность его коррекции Journal of Education, Health and Sport. 2016;6(10):520-533. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.167128 http://ojs.ukw.edu.pl/index.php/johs/article/view/4002 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. УДК 599.23+591.471:615.038 МОРФОГЕНЕЗ КІСТОК СКЕЛЕТУ ЩУРІВ НА ТЛІ ТРИВАЛОГО ВЖИВАННЯ ТАРТРАЗИНУ ТА МОЖЛИВОСТІ ЙОГО КОРЕКЦІЇ Галина Володимирівна Лук’янцева Національний університет фізичного виховання і спорту України, Київ Реферат Мета: вивчити гістологічну будову проксимального епіфізарного хряща кісток білих щурів після 2-місячного вживання в їжу тартразину в різній концентрації й обґрунтувати можливості його корекції натрію селенітом. Матеріал: дослідження проведено на білих безпородних статевозрілих щурах-самцях репродуктивного періоду онтогенезу з вихідної масою тіла 200-210 г. Результати: з’ясовано, що тривале введення тартразину білим щурам супроводжується порушенням гістологічної будови проксимального епіфізарного хряща плечових і тазових кісток, а також третього поперекового хребця. Висновки: вираженість ефекту носить дозозалежний характер (введення тартразину в дозі 1500 мг/кг супроводжується більш значним порушенням гістологічної будови хрящів, ніж застосування барвника у дозі 750 мг/кг). Доведено, що в період реадаптації після введення тартразину застосування натрію селеніту супроводжується відновленням гістологічної будови хрящів. Ключові слова: тартразин, хрящі, натрію селеніт. MORPHOGENESIS BONES RATS AGAINST LONG TARTRAZINE USE AND POSSIBILITIES OF ITS CORRECTION Lukjantseva Galina National University of Physical Education and Sport of Ukraine, Kyiv Abstract Objective: To study the histological structure of the proximal epiphyseal cartilage bone white rats after 2 months consumption tartrazine in different concentrations and justify its possible correction of sodium selenite. Material: The study was conducted on white outbred mature male rats reproductive period ontogeny of initial body weight 200-210 g. Results: found that prolonged administration tartrazine white rats is accompanied by histological structure of the proximal epiphyseal cartilage of the shoulder and pelvic bones, and the third lumbar vertebra. Conclusions: The severity of the effect is dose-dependent nature (tartrazine administration at a dose of 1500 mg/kg is accompanied by a significant violation of the histological structure of cartilage than the use of the dye at a dose of 750 mg/kg). Proved that during rehabilitation after administration of sodium selenite tartrazine application accompanied by restoration of histological structure of cartilage. Keywords: tartrazine, cartilage, sodium selenite. МОРФОГЕНЕЗ Костей СКЕЛЕТа крыс НА фоне длительного употребления ТАРТРАЗИНа и возможность его КОРрЕКЦии Галина Владимировна Лукьянцева Национальный университет физического воспитания и спорта Украины, Киев Реферат Цель: изучить гистологическое строение проксимального эпифизарного хряща костей белых крыс после 2-месячного употребления в пищу тартразина в разной концентрации и обосновать возможности его коррекции натрия селенитом. Материал: исследование проведено на белых беспородных половозрелых крысах-самцах репродуктивного периода онтогенеза с исходной массой тела 200-210 г. Результаты: установлено, что длительное введение тартразина белым крысам сопровождается нарушением гистологического строения проксимального эпифизарного хряща плечевых и тазовых костей, а также третьего поясничного позвонка. Выводы: выраженность эффекта носит дозозависимый характер (введение тартразина в дозе 1500 мг/кг сопровождается более значительным нарушением гистологического строения хрящей, чем применение красителя в дозе 750 мг/кг). Доказано, что в период реадаптации после введения тартразина применения натрия селенита сопровождается восстановлением гистологического строения хрящей. Ключевые слова: тартразин, хрящи, натрия селенит.